Purely Cystic Desmoplastic Ganglioglioma: An Incidental Finding in a Giant Cyst - Sumit Bansal; Ashok Kumar Mahapatra; Susama Patra; Radhamohan Gharei (Indian Journal of Neurosurgery, 2017)
Desmoplastic infantile ganglioglioma (DIG) is a rare supratentorial brain tumor occurring mostly before the age of 2 years. It has a good prognosis and total excision of the tumor is curative, necessitating no further treatment. An accurate pathologic diagnosis is crucial. Until now, approximately 70 cases of this tumor type have been reported. Solid-cystic variety is mostly described with occasional purely solid type lesion also. We are presenting a 12-month-old male infant with developmental delay and a giant cyst on the right side of supratentorial compartment, which showed histological features of desmoplastic ganglioglioma. Hence, the current case is reporting the rare histologic finding of cystic change in desmoplastic ganglioglioma. Cystic form of desmoplastic ganglioglioma should be considered in differential diagnosis of supratentorial cystic lesion in an infant. Prognosis is excellent after complete excision.